1988
DOI: 10.1002/ange.19881001134
|View full text |Cite
|
Sign up to set email alerts
|

Ein neuer Typ kationischer Wirtmoleküle mit π‐Acceptor‐Eigenschaften

Abstract: Der Templateffekt eines Kohlenwasserstoffs konnte überraschend erstmals nachgewiesen werden: Bei der Eintopfsynthese des tetrakationischen Makrocyclus 1c steigt die Ausbeute von 3–5% auf 16%, wenn Phenanthren im Überschuß zugegen ist. Als neue π‐Acceptor‐Wirtverbindungen nehmen die phanartigen Tetrakationen 1a–1c und 2a–2c Arene als π‐Donoren sandwichartig in ihren Hohlraum auf. magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[11] Me2SO, [12] N.N-Dimethylformamide/10% Me2SO. [13] A/.AADimethylformamlde. [14] Dichloromethane.…”
Section: Structures Of Cyclophanes and Their Complexes With Aromatic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Me2SO, [12] N.N-Dimethylformamide/10% Me2SO. [13] A/.AADimethylformamlde. [14] Dichloromethane.…”
Section: Structures Of Cyclophanes and Their Complexes With Aromatic ...mentioning
confidence: 99%
“…The major groove opening of 12 is ideal to shape an aromatic binding site in chiral cyclophane hosts. Starting from optically pure (R)-and (S)-7,7'-di(benzyloxy)-2,2'-dihydroxy-l,l'-binaphthyl (13), optically resolved through simple clathrate formation with quinine, the two enantiomers of cyclophane 14 were prepared (46). The 'H NMR complexation studies in UvO/methanol-a'i (60:40 v/v, T = 293 K) showed that the naproxen derivatives (R,£>)-6ad form diastereomeric 1:1 complexes of differential geome-try and stability with the host enantiomers (R)-and (S)-14.…”
Section: Complexation Of Arenes In Organic Solventsmentioning
confidence: 99%